Junior High School Students Science Literacy Profile on the Issue of Environmental Pollution in Contextual Learning - Findiyas Azizah Nurfadhilah; Fida Rachamadiarti; Endang Susantini; Siti Masruroh (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
Science literacy skills (SLS) is essential for individuals to understand scientific phenomena, evaluate information critically, and make appropriate decisions in addressing increasingly complex real life problems. However, based on previous research, students’ science literacy are still classified as low to moderate, so it is necessary to re-examine. This study aims to analyse the science literacy profiles of lower secondary school students through the issue of environmental pollution in contextual learning. This study employs a non-experimental design using a census method involving 251 Year VII students at SMPN 1 Waru. The research instrument consists of 10 multiple choice questions developed based on three indicators of science literacy, namely explaining phenomena scienceally, evaluating science investigations, and using science evidence for decision making. The instrument was validated by science experts and practitioners with a reliability of 0.996 (very high). Data analysis was conducted descriptively by assigning scores, calculating the percentage of achievement for each indicator, and categorising them based on predefined criteria. The research results indicate that students’ SLS generally remain in the low category. The highest scores were found in the ability to explain phenomena scienceally (57.47%), evaluate science investigations (54.18%), and the lowest was in the use of science evidence (49.4%). Further analysis indicates that students tend to be better able to answer contextual questions and those based on conceptual understanding but still struggle to evaluate data and use science evidence critically. These findings underscore the importance of implementing contextual learning that links science concepts to real world problems